Are Happy Workers More Productive? The Mediating Role of Service-Skill Use - Salas-Vallina, Andrés; Pozo-Hidalgo, Manoli; Gil-Monte, Pedro R. (Frontiers in Psychology, 2020)
The purpose of this paper is to examine the relationship between happiness at work and cross-selling performance in the banking sector. In addition, the mediating effect of service-skill use is analyzed in the relationship between happiness at work and performance. Confirmatory factor analysis is used by means of structural equation models to assess the relationship between happiness at work, service-skill use and cross-selling performance. A sample of 492 financial service employees is examined. Results reveal that happiness at work positively and directly affects cross-selling performance. The study also shows that service-skill use plays a partial mediating role in the relationship between happiness at work and cross-selling performance. This research expands the theory of the happy productive worker perspective based on the job demands-resources model, and defines and conceptualizes service-skill use. Employees who are happier at work cross-sell better, but their service-skill use mediates the effect of happiness at work on cross-selling performance.